Studi Pertumbuhan dan Daya Hasil Empat Galur Tomat (Lycopersicum esculentum Mill) di Dataran Rendah - Renti Marlia Putri; Adiwirman '; Elza Zuhry (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
While higher productivity can be achieved if the tomato seedlings were taken from new varieties that have adapted to the agro-climate. To produce new varieties that have high productivity and stability require gene sources of plant traits that support these objectives, this can be achieved through plant breeding programs. This study aimed to observe the growth and yield of four tomato strains grown in low-lying areas with comparable varieties of Intan and Ratna. Research carried out at the This study used a randomized block design with six treatments of tomato genotypes and 3 replications. Genotypes were tested for the T33-IPB 1-3, IPB T57-3, T60-IPB 2-6, IPB-8b 2201-5. Check varieties ie Intan and Ratna.The parameters measured were plant height, stem diameter, days to flowering, harvest, fruit length, fruit diameter, flesh thickness, fruit cavity number, weight per fruit, total fruit weight per plant and number of seeds per gram. The results showed that of all genotypes tested significantly affected the growth and yield of plants. Significantly different genotypes tested to date of flowering, maturity, plant height, stem diameter fruit length, fruit diameter, flesh thickness, fruit cavity number,weight per fruit, number of seeds per gram and total fruit weight per plant.. The results of the total weight per plant was highest in genotype-IPB 1-3 T33 and T57 followed IPB-3 genotype and the lowest total weight per plant was found in 2201 IPB-58B genotype and Ratna varieties followed.Technical Services Unit of the Faculty of Agriculture in October until February 2013.Keyword: Tomatoes, Genotypes, growth and yield, lowlands